Clinical importance of acquired cystic disease of the kidney in patients undergoing dialysis. Issue 6408 (17th December 1983) - Ratcliffe, P J; Dunnill, M S; Oliver, D O
Abstract : From 1976 to 1982 five patients undergoing haemodialysis at Oxford Renal Unit suffered serious complications from acquired cystic disease of the kidney and two died as a direct result. Clinical features seen were pain, haematuria, palpable renal enlargement, massive haemorrhage, resolution of anaemia, and metastatic malignancy. The clinical histories emphasise the features of a disease that is likely to assume increasing importance in patients undergoing haemodialysis.